Linking CD11b+ Dendritic Cells and Natural Killer T Cells to Plaque Inflammation in Atherosclerosis. (9th March 2016) - Rombouts, Miche; Ammi, Rachid; Van Brussel, Ilse; Roth, Lynn; De Winter, Benedicte Y.; Vercauteren, Sven R.; Hendriks, Jeroen M. H.; Lauwers, Patrick; Van Schil, Paul E.; De Meyer, Guido R. Y.; Fransen, Erik; Cools, Nathalie; et al.
Abstract : Atherosclerosis remains the leading cause of death and disability in our Western society. To investigate whether the dynamics of leukocyte (sub)populations could be predictive for plaque inflammation during atherosclerosis, we analyzed innate and adaptive immune cell distributions in blood, plaques, and lymphoid tissue reservoirs in apolipoprotein E-deficient (ApoE −/− ) mice and in blood and plaques from patients undergoing endarterectomy. Firstly, there was predominance of the CD11b + conventional dendritic cell (cDC) subset in the plaque. Secondly, a strong inverse correlation was observed between CD11b + cDC or natural killer T (NKT) cells in blood and markers of inflammation in the plaque (including CD3, T-bet, CCR5, and CCR7). This indicates that circulating CD11b + cDC and NKT cells show great potential to reflect the inflammatory status in the atherosclerotic plaque. Our results suggest that distinct changes in inflammatory cell dynamics may carry biomarker potential reflecting atherosclerotic lesion progression. This not only is crucial for a better understanding of the immunopathogenesis but also bares therapeutic potential, since immune cell-based therapies are emerging as a promising novel strategy in the battle against atherosclerosis and its associated comorbidities. The cDC-NKT cell interaction in atherosclerosis serves as a good candidate for future investigations.